"Moonlighting" GAPDH Protein Localizes with AMPA Receptor GluA2 and L1 Axonal Cell Adhesion Molecule at Fiber Cell Borders in the Lens. (2nd January 2016) - Frederikse, Peter H.; Nandanoor, Anoop; Kasinathan, Chinnaswamy
Abstract: Purpose: The canonical role of glyceraldehyde phosphate dehydrogenase (GAPDH) is as an enzyme in glycolysis. GAPDH is also a principal "moonlighting" protein with additional roles at diverse sites in a variety of cells. Surface GAPDH on mammalian, yeast, and bacterial cells acts as a receptor and also mediates cell contacts. In neurons, extracellular GAPDH localizes at synapses. Two GAPDH binding partners at synapses are α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptor (AMPA) GluA2 subunit at dendritic spines and L1 cell adhesion molecule at pre-synaptic membranes, and both proteins are also expressed in lenses. Fiber cell membrane protrusions and dendritic spines have similar size, shape, and spacing, contain F-actin, and express clathrin/AP-2 Adaptor at their surfaces linked with Tyr-phosphatase STEP-regulated endocytosis of AMPA/GluA2 receptors. AMPA receptors work with NMDA ( N -methyl-d -aspartate) and GABA (γ-aminobutyric acid) receptors, calcium calmodulin kinase II (CaMKIIα), channel proteins, STEP, and ephrin receptors, which are also expressed in lenses. In neurons, coordinate AMPA/GluA2 receptor endocytosis with GAPDH is linked with disease. GAPDH was previously characterized as a fiber cell membrane protein and shown to decrease substantially in interior fiber cells in human age-related cataract. Here, we examined GAPDH spatial expression in healthy lenses in two vertebrate species. Methods: In situ methods were used to examine GAPDH expression in lenses of healthy young adult rabbits and chickens. Immunoblots were used to detect L1 in lenses. Results: The present study demonstrated that GAPDH is present at fiber cell borders in adult rabbit and chicken lenses with evidence of focal concentrations along the fiber cell perimeter, and overlapped with detection of p-Tyr-GluA2, L1, STEP, actin and clathrin. We observed that L1-140 kDa was the prominent form in lens. Conclusions: Our findings indicate investigations into GAPDH "moonlighting" activities similar to its role in cell–cell interactions at neuron surfaces are warranted in the lens.